Characterization of boron carbide particles and its shielding behavior against neutron radiation - Kipcak, A. Seyhun; Gurses, Pelin; Derun, Emek M.; Tugrul, Nurcan; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Boron minerals, considered future essential materials, can be used as raw materials in the production of boron carbide. In this study, boron carbide, the hardest material after diamond and cubic boron nitride, is characterized and the neutron shielding behavior is investigated. The characterization and structural evaluation of the boron carbide sample was performed using X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FT-IR) and Raman Spectroscopy. In addition, a neutron Howitzer was used to measure the neutron permeability of boron carbide samples of various thicknesses. The sample composed of 12.5 g of boron carbide powder and 3 g of Wax (R) had the lowest neutron permeability rate (62.1%). Pellet 3 had the smallest total macroscopic cross section of boron carbide particles, 0.722 +/- 0.0071 cm(-1). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Boron carbide; XRD; FT-IR; Raman; Neutron permeability; BISMUTH; Thermodynamics; Energy & Fuels; Mechanics